Assessing and responding to hazardous and risky alcohol and other drug use: The practice, knowledge and attitudes of staff working in mental health services. (June 2014) - Wheeler, Amanda; Crozier, Michelle; Robinson, Gail; Pawlow, Natale; Mihala, Gabor
<x xml:space="preserve">Abstract</x> Introduction: Comorbidity of mental illness and alcohol and other drugs (AOD) raises workforce challenges in terms of appropriate knowledge, skills and attitudes required for delivering best care. Aim: (1) To assess the knowledge, skills and attitudes of mental health staff in relation to AOD use and (2) to inform development of training to provide effective screening and interventions for people with both mental health and AOD problems (co-morbidity). Method: Quantitative survey of knowledge, skills and attitudes regarding AOD issues completed by multidisciplinary mental health staff (n = 104/218) working across acute and community settings. Results: A 47.7% response rate was achieved. Generally staff held positive attitudes and motivation towards working with people with comorbidity, but there was an absence of formal training, experience or knowledge. Most staff believed they could deal with AOD issues; however, confidence was higher with assessment over AOD-related interventions (brief interventions, motivational approaches and goal setting) and only 24% of staff correctly identified standard drinks. Most staff recognized that AOD assessment and intervention is part of their role and access to training would facilitate their ability to improve service to mental health consumers. Conclusion: Integrated care for people with comorbidity requires mental health service providers to address identified gaps in clinician's knowledge, skills and attitudes with training in relation to AOD. To ensure effective training uptake and implementation, workforce leaders need to target identified barriers with initiatives such as support, mentoring and appropriate tools in relation to AOD.